An Evolutionary Approach to Hierarchy of Effects Model and its impact on Creative Marketing - Selvarajan, P. (University of Sri Jayewardenepura, 2011)
The purpose of this research study is to review a large body of literatures of hierarchy of effects which has accumulated over several decades influencing the marketing function creatively and innovatively. The first review describes the traditional hierarchy models followed by the discussion of alternative-order hierarchy models. Many marketers know the hierarchy of effects, but usually by a different name like AIDA, demand chain and the purchase funnel. It is a hierarchy of effects since at each stage marketers must achieve different communication goals. They might be encouraging trial, rewarding loyalty or communicating brand associations, depending on the stage the target customer has reached. It is impossible what the stages and goals will be in each marketer’s hierarchy since every brand is different. However the stages can include awareness, preference, purchase and hopefully loyalty. This research study is a theoretical and empirical analysis of the hierarchy of effects and the findings showed the impact of traditional hierarchy framework which hypothesizes that the audiences respond to messages in a cognitive, affective and conative sequence on modern hierarchy of effects models. However the models might be in different sequence for different kinds of products. Further the researcher also found that the hierarchies of effects models were unique to organizations in different industries in achieving different objectives and to understand the post purchase reactions of consumers. Finally the researcher proposed a hierarchy of effects model which is suitable for Sri Lankan marketers since the word of mouth communication is a powerful marketing communication tool in Sri Lanka. It is recommended since the model of hierarchy of effects highly impacted on integrated marketing communication, it should be understood by the marketers for making the whole marketing activities be creatively and innovatively for the success.
Keywords: Hierarchy of Effects; Cognition; Affect; Conation; Creative Marketing